Boganmeldelser - Elholm, Thomas; Svensson, Kerstin; Olaussen, Leif Petter; Kongstad, Annalise; Bech, Charlotte Mathiesen; Kyvsgaard, Britta (Nordisk Tidsskrift for Kriminalvidenskab, 2006)
Book reviews